Thick Graft Versus Double-Bundle Technique on Posterior Cruciate Ligament Reconstruction: Experimental Biomechanical Study with Cadavers - João Alberto Ramos Maradei-Pereira; Alexandre Estevão Vamos Kokron; César Augusto Martins Pereira; Marco Martins Amatuzzi (Revista Brasileira de Ortopedia, 2019)
Abstract Objective To evaluate the biomechanical effect of graft thickness compared with the double-bundle technique on posterior cruciate ligament (PCL) reconstruction in human cadaveric knees. Methods A total of 9 human cadaveric knees were tested in 5 conditions: intact knee (INT); single-bundle reconstruction with a 10-mm quadriceps tendon (SB); double-bundle reconstruction with a 10 mm-quadriceps tendon for the anterolateral bundle and a 7-mm doubled semitendinosus tendon for the posteromedial bundle (DB); single-bundle reconstruction with a 10-mm quadriceps tendon plus a 7-mm doubled semitendinosus tendon (SBT); and PCL-deficient (NoPCL). The posterior tibial translation (PTT) was measured in response to a 134-N posterior tibial load at 0º, 30º, 60º e 90º of knee flexion. Results The PTT values of the DB and SBT techniques were always significantly lower (better stability) than those of the SB technique. The PTT values of the SBT technique were significantly lower than those of the DB technique at 60º (p = 0.005) and 90º (p = 0.001). Conclusions Graft enlargement improves knee stability in isolated PCL reconstructions, whereas the graft division in the two-bundle technique worsens this stability at 60º and 90º of knee flexion. The findings of the present study suggest that knee stability in PCL reconstructions may be improved with the use of thicker grafts in the SB technique rather than performing the DB technique.